GANTI KERUGIAN TERHADAP KORBAN KECELAKAAN LALU LINTAS BERDASARKAN UU NO.22 TAHUN 2009 (STUDI PUTUSAN PENGADILAN TINGGI YOGYAKARTA NOMOR: 10/ PDT/ PT YYK) - Ghina Ramadhania Poetri; Amad Sudiro (Fakultas Hukum Universitas Tarumanagara, 2021)
Traffic accidents inevitably take victims who feel harmed by certain parties. Traffic accident victims have the right to get compensation by the party responsible for the cause of the traffic accident. The driver who commits an unlawful act that causes a traffic accident that causes harm to the victim must compensate for the loss that has violated the law and caused a loss, then he is obliged to compensate for the loss. This research discusses compensation for victims of traffic accidents based on law number 22 of 2009. The problem faced is What is the legal responsibility system for traffic accident victims based on Law Number 22 of 2009. In addition, how to settle compensation for victims of traffic accidents in the Yogyakarta High Court Decision Number: 10/ Pdt/ Pt Yyk. The research method used is a normative juridical research method. The results show that in the system of legal responsibility for victims of traffic accidents based on Law number 22 of 2009 namely by providing compensation in accordance with criminal provisions in accordance with court decisions and providing sanctions against the Defendant. In this case, if the victim of a traffic accident wants to claim compensation for the losses he suffered, he can combine the case to be filed in a civil lawsuit.